Pendekatan Deep Learning: Transformasi Mindful, Meaningful, dan Joyful dalam Pembelajaran Holistik - Yona Azzahra; Christian Arief Jaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Deep learning approach in education represents a new direction in learning that emphasizes deep thinking, reflective awareness, and emotional engagement of learners. It is grounded in three main pillars: mindful learning, meaningful learning, and joyful learning, which together foster holistic learning experiences. This article aims to examine the integration of these three pillars through a literature review of 20 academic articles published between 2020 and 2025. The findings indicate that the implementation of deep learning can enhance contextual understanding, increase learning motivation, and strengthen the connection between learning and real-life situations. However, its implementation in the field still faces several challenges, including limited infrastructure, inadequate teacher training, and the persistence of conventional teaching practices. Therefore, optimizing the deep learning approach requires progressive educational policies and continuous teacher capacity development to support the creation of learning that is conscious, meaningful, and joyful aligned with the demands of 21st-century education.